An asymmetric three-component reaction of a diazo compound with an alcohol and a seven-membered imine. Issue 8 (7th March 2022) - Xie, Xiongda; Bao, Ming; Chen, Kewei; Xu, Xinfang; Hu, Wenhao
Abstract : An asymmetric three-component reaction via Mannich-type interception of an oxonium ylide with a 7-membered imine has been disclosed, providing chiral dibenzoazepine analogues with excellent stereoselectivity and structural diversity. Abstract : A dirhodium and chiral phosphoric acid co-catalyzed asymmetric three-component reaction of a diazo compound with an alcohol and a seven-membered imine has been developed via Mannich-type interception of a transient oxonium ylide. This reaction provides an efficient approach for the synthesis of chiral dibenzoazepine analogues, including dibenzo[ b, f ][1, 4]oxazepine, dibenzo[ b, f ][1, 4]thiazepine, and dibenzo[ b, e ]azepine derivatives, in generally good yields with excellent stereoselectivity (91%–99% ee) under mild reaction conditions. This reaction shows broad substrate generality, and these generated products could be further converted to enantioenriched tetracyclic frameworks with embedded functional groups.